Hospital information system-based pharmacovigilance for elderly patients: practices and results - Zhou, Nan; Fang, Zhiyuan; Liang, Dong; Lian, Jiangping; Han, Huan; Li, Rui (Journal of the Pakistan Medical Association, 2023)
Objectives: To evaluate the effect of a pharmacovigilance system on potentially inappropriate medication prescriptions for elderly patients. Method: The retrospective study was conducted at Shaanxi Provincial People’s Hospital, China, after approval from the ethics review committee, and comprised data from May 2020 to April 2021, and comprised prescriptions related to elderly patients aged at least 65 years. Number of medication risk assessment entries, number of intervened medical orders on outpatients and inpatients number of medical order prompts, and number of physician communication with prescription-checking pharmacists were noted. Potential drug interaction rate was compared between pre- implementation from May to October 2020 and post-implementation from November 2020 to April 2021. Besides, the usage of sedatives and hypnotics and potentially inappropriate medication was noted for the period from January to June 2021 to evaluate the sustained effect of pharmacovigilance system. Data was analysed using SPSS 19. Results: A total of 118 drugs were involved in the 3911 entries of outpatient prescription warnings, of which 19 drugs accounted for 3156 (80%). Besides, a total of 113 drugs were involved in the 3999 entries of inpatient prescription warnings, of which 19 drugs accounted for 3199 (80%) The overall prevalence of potentially inappropriate medication related to sedatives and hypnotics decreased post-intervention as warning percentage was 16.1% in January and 6.7% in June among outpatients. On inpatients, the warning percentage was 30.6% in January and 6.1% in June. Conclusions: The pharmacovigilance system could reduce potentially inappropriate medication and provide deeper technical support for the safety of medical behaviour and individualised treatment of patients. Key Words: Pharmacovigilance, Drug safety, Potentially inappropriate medication, Elderly patients, Risk management.